Political participation of women in Kaduna State, Nigeria - Mohammed, Abubakar (2015)
Women political participation has become an issue of concern due to current records that are indicating low participation and under representation in both elective and appointive positions in Nigeria. Although, in recent years, research findings and literatures have confirmed that there is an increase in the level of women's participation in the Nigerian politics and the political process, but yet,their participation and representation is still relatively low. This research aimed to look at the women political participation trend in Nigeria and explore some of the factors that influence or encourage women to participate in politics and also to find out some of the obstacles to their political participation in Kaduna state,Nigeria. The research employed qualitative method as its major research technique. In-depth interview was conducted with nine (9) research informants that were being selected from the three (3) central zones of Kaduna State. The collect regarding the trend of women's political participation in Nigeria shows that, women participated actively in politics and in the decision making process in the pre-colonial period, but during the colonial time, the research ascertained that women were denied right to Franchise and that consequently affect their present participation in politics and the political process. Regarding factors that influence or encourage women participation, the data shows that, interest,political awareness and reservation of political position were among the factors that can positively influence women‟s participation in politics. The research also shows that, Nigerian culture, religion, political violence, socioeconomic status of women were among the obstacles to the women political participation in Kaduna state in particular and Nigeria at large. The research recommends that the government should introduce a special program that will attract women to develop an interest via participating in the country‟s politics and also special awareness and sensitization campaign on the imperativeness of women‟s participation should be introduced by the government or other related agencies. The research also recommends that women should be empowered economically through programs that aimed at bridging gaps between female and male. The Nigerian government should find a way through which political violence can be eliminated in Nigerian politics by creating employment opportunities to youth who are mostly used as a tool for political violence.